Center-Pivot-Irrigated Soybean Cost-Return Budget - O'Brien, Daniel M.; Dumler, Troy J.; Thompson, Curtis R.; Stockton, Roger (My University, 2002)
This publication projects a budget that reflects expected income and costs based on center-pivot-irrigated soybean production in Kansas.
MF586_2002_10
Keywords: MF586; Economics; Crops; MF